Synergic effect of thermo-chemical pretreatment of waste-activated sludge on bio-methane enhancement - Almegbl, A. M.; Munshi, F.; Khursheed, A. (Frontiers in Environmental Science, 2024)
Sustainable and environmentally friendly energy production is feasible via anaerobic digestion (AD) of organic wastes, such as waste-activated sludge (WAS). However, due to its limited degradation, a pretreatment strategy is applied to WAS to enhance its bio-degradation and, thus, biogas yield. Alkaline (0.5-9% g NaOH/gTS, 30 min), microwave (MW) (90- 175 °C), and hybrid (0.5% gNaOH/gTS + 125 °C) pretreatments were applied to WAS. Characterization of untreated and pretreated WAS revealed that with higher alkaline and MW pretreatment, the soluble chemical oxygen demand (sCOD), carbohydrate, and protein increased; however, the readily biodegradable COD (rbCOD) rate was unlike the sCOD. The sCOD was 6.7-17.6%, 8-23.1%, and 37% for alkaline, MW, and hybrid pretreatments, respectively. Stronger alkaline and MW pretreatment induced higher turbidity, capillary suction time, and lower average particle size. AD of alkaline, MW, and hybrid pretreated WAS produced 93.8% (0.5% NaOH), 125.2% (MW at 125 °C), and 198.7% (0.5% NaOH and MW at 125 °C), respectively, increased biogas compared to the AD of untreated sludge. The AD data of the alkaline, MW, and hybrid pretreated BMP assays fitted well with the modified Gompertz model with a coefficient of determination above 0.95. The PCA analysis showed that biogas production is closely correlated with pretreatment temperature, VFA production, rbCOD, sCOD, and soluble carbohydrates and protein. Microbial genome sequencing analysis showed improvement in microbial abundance and diversity. Acetoclastic methanogen (Methanothrix) growth was improved by 37.3% (MW pretreatment). Abundances of Methanosarcina, using all three metabolic pathways for methanogenesis, were 16.7, 20.7, 10.5, and 47.8% in control, alkaline, MW and hybrid pretreated digestate, respectively, corresponding to 186% improvement in hybrid pretreatment when compared to control.